2011
DOI: 10.1016/j.geb.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Collusion, agglomeration, and heterogeneity of firms

Abstract: Jehiel (1992) and Friedman and Thisse (1993) show that spatial agglomeration appears in a standard two-stage location price model if symmetric firms collude in prices. We introduce a cost difference between two firms. We show that agglomeration never appears in a collusive equilibrium even when the cost difference between firms is sufficiently small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In this paper, we restrict our attention to the symmetric case and symmetric equilibrium. In the context of spatial competition, the cost asymmetry often leads to some curious results (Liang and Mai, ; Matsumura and Matsushima, , , ; Meza and Tombak, ). Extending our analysis of FMS to the asymmetric cost structure is a task that remains for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we restrict our attention to the symmetric case and symmetric equilibrium. In the context of spatial competition, the cost asymmetry often leads to some curious results (Liang and Mai, ; Matsumura and Matsushima, , , ; Meza and Tombak, ). Extending our analysis of FMS to the asymmetric cost structure is a task that remains for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Matsushima (2004Matsushima ( , 2009 show that when the transport costs faced by the upstream firms are small or the difficulty in converting inputs to the final goods is low (which are comparable to our case with no transportation cost faced by the upstream firms or no difficulty in converting inputs to the final goods), the firms prefer maximal differentiation. Considering bilateral bargaining between the input supplier and the final goods 3 Matsumura and Matsushima (2011) show that minimal differentiation does not occur in a collusive equilibrium if the firms differ in costs. 4 Although majority of papers using the Hotelling framework consider that firms locate within the "Hotelling line", there are papers which don't restrict firms to locate within the Hotelling line.…”
Section: Introductionmentioning
confidence: 99%
“…Even a slight cost difference can change the result drastically. For example, Matsumura and Matsushima (2011) showed that even a slight cost difference changes the property of equilibrium location in location‐collusion models.…”
mentioning
confidence: 99%